2013
DOI: 10.1111/jgs.12372
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Effective Characteristics of Nursing Homes and Other Residential Long‐Term Care Settings for People with Dementia

Abstract: OBJECTIVES:In response to the need for an evidencebased review of factors within long-term care settings that affect the quality of care, this review compared characteristics of nursing homes and other residential long-term care settings for people with dementia and their informal family caregivers with respect to health and psychosocial outcomes. DESIGN: Databases were searched for literature published between 1990 and March 2012 that met review criteria, including that at least 80% of the subject population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 25 publications
3
53
0
3
Order By: Relevance
“…22 There is little evidence that having special care results in better outcomes. 6,7,23 However, it is worth noting that the national data reported here indicate that there are more licensed staff working on these units than in other assisted living residences.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…22 There is little evidence that having special care results in better outcomes. 6,7,23 However, it is worth noting that the national data reported here indicate that there are more licensed staff working on these units than in other assisted living residences.…”
Section: Discussionmentioning
confidence: 70%
“…Residents with worse cognition and ADL functions generally experience poorer quality of life, but that quality is influenced more by considerations other than individual characteristics. 33 For example, other studies 7 have found that pleasant sensory stimulation and using protocols for individualized care to improve function result in better outcomes. Thus, assisted living residences that embrace such practices may be preferred to residences that do not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I stortingsmeldingen «Morgendagens omsorg» (Meld. St. 29 (2012−2013, 2013) blir det imidlertid pekt på at samhandlingen med pårørende ofte er mangelfull og tilfeldig, og det etterlyses mer forskning som grunnlag for nye måter å samarbeide på. Spørsmålet er hvilket innhold og kvaliteter som vil vaere av betydning i støtten av pårørende.…”
Section: Bakgrunnunclassified
“…St. 29 (2012−2013), 2013. Mange land satser på mer hjemmetjenester som en løsning, og prioriterer de eldste og personer med de mest uttalte behov for 24 timers pleie og omsorg til sykehjem (OECD, 2005).…”
Section: Introduksjonunclassified